Developing Online Laboratory as an English Learning Media for Muhammadiyah Schools in Bantul Regency - Purbohadi, Dwijoko; Wijaya, Titis Wisnu; Aditya, David Sulistiawan (Universitas Muhammadiyah Surakarta, 2023)
The Online Language Lab is an innovation aimed at revitalizing English language practice activities in schools, replacing the analog language labs that have long been abandoned by many schools in Indonesia. It is known that English language learning focused only on materials such as reading, pronunciation, and speaking without practice can hinder students' ability to communicate effectively in English. We have successfully developed an internet-based Online Language Lab by combining several supporting technologies, including Learning Management System (LMS), speech to text converter, text to speech converter, p5 JavaScript library, Moodle app, and SCORM, to create an interactive online language lab. Students can learn English independently with learning modules tailored to their respective abilities. Our Online Language Lab system has been tested in a school to measure its usability, and the results were very positive. In addition, we also conducted experiments to assess the feasibility of our system and the results showed that it can be implemented widely in various schools in Indonesia. It is expected that with the Online Language Lab, students can significantly improve their English language skills and be better prepared to face global challenges in the future. This is a crucial breakthrough in improving the quality of English language education in Indonesia.